Politik Hukum Pembentukan Peraturan Perundang-Undangan dengan Pancasila sebagai Rechtsidee (SETARA : Jurnal Ilmu Hukum, 2018)
The philosophical paradigm values in the formation of laws and regulations as legal norms contain the awareness, appreciation of values, attitudes, ideas, and concepts of political authorities. Pancasila, as the soul of the nation and as the legal ideal (rechtsidee), is a source of law in the formation of legislation. Theoretically, the formation of legislation is based on the legal norms of society, while juridically, constitutional amendments affect the formation of legislation. Paradigm changes influence the legal politics of forming laws and regulations and affect their implementation in society. The authority to form laws and regulations, which was previously held by the President, has shifted to the House of Representatives. Legal politics cannot be separated from Pancasila as rechtsidee, which serves as the basis for advancing the nation and state in accordance with the nation's culture.